Bimbingan Agama bagi Narapidana di LAPAS Kelas IIA Ambon - Jumail Jumail (Al-Ittizaan: Jurnal Bimbingan Konseling Islam, 2021)
Religious guidance is a flagship program that is run at correctional institutions to equip prisoners with religious knowledge. One of the benefits of this implementation is to provide changes in the behavior of prisoners so that they can return to the right path. The purpose of this study is to describe the mechanism for implementing religious guidance activities carried out in Class IIA Ambon Prisons. The research method used in this study is qualitative with a psychoreligious approach. Eight informants were selected through a snowball sampling pattern. .The results of the study show that the implementation of religious guidance held in Class IIA Ambon Prisons focuses on several elements; a) mentoring activities, b) assisted materials, and c) activity implementation teams. as far as its implementation, the religious guidance that has been carried out has been carried out well, but there are some obstacles faced, namely; the ustadz and ustadz who guide have not been given time due to the covid-19 pandemic so that the implementation is still not running as usual and allocation the guidance time is still relatively lacking, so it is necessary to add more time or days so that the implementation is more optimal.